Reconstruction Of Child Protection Paradigm Based On Islamic Values Through The Co-Creation Model Of Lakpesdam PWNU NTB - Muh Alwi Parhanudin; Agus Dedi Putrawan; Miptahudin Khairi; Fira Hilmanisa; Assazali Sibawaihi (Politea : Jurnal Politik Islam, 2026)
This study discusses the reconstruction of the child protection paradigm based on Islamic values implemented by the Research and Human Resource Development Institute (Lakpesdam) of PWNU NTB through the Co-Creation model in North Lombok Regency, West Nusa Tenggara. Departing from the sociological anomaly where high religiosity does not correlate with low rates of sexual violence and child marriage (NTB ranks first nationally in child marriage at 17.32%), this research aims to analyze the construction of the Co-Creation paradigm, the multi-stakeholder collaboration mechanism, and the synergy of local Sasak wisdom. The research employs an interpretative-constructivist paradigm with a qualitative case study approach. Data were collected through in-depth interviews with 18 key informants, participatory observation for three months, documentation analysis, and Focus Group Discussions (FGDs) in four inclusive villages (Malaka, Pemenang Barat, Teniga, Bayan). The findings show that Lakpesdam's Co-Creation model is built on four pillars of Islamic values (Aswaja, Mabadi Khairul Ummah, mustad'afin, and maqasid al-shariah). The model successfully transforms village public policy through advocacy strategies. Proposals from vulnerable groups included in the Village Government Work Plan (RKPDes) for 2024 totaled more than IDR 600 million, with the largest allocation in Bayan Village at IDR 279.36 million for the Digital Village program. The increase in reported child violence cases from 120 (2023) to 141 (2024) is interpreted not as a failure but as an indicator of the success of deconstructing social taboos. This research contributes to the development of contemporary maqasid al-shariah theory in the context of child protection and a model of Islam-based co-governance in Muslim Indonesian society